Benefits and harms of antihypertensive treatment in low-risk patients mild hypertension - Sheppard, JP; Stevens, S; Stevens, R; Martin, U; Jonathan, M; Hobbs, FDR; McManus, R (American Medical Association, 2018)
Importance: Evidence to support initiation of pharmacologic treatment in low-risk patients with mild hypertension is inconclusive, with previous trials underpowered to demonstrate benefit. Clinical guidelines across the world are contradictory. Objective: To examine whether antihypertensive treatment is associated with a low risk of mortality and cardiovascular disease (CVD) in low-risk patients with mild hypertension. Design, setting, and participants: In this longitudinal cohort study, data were extracted from the Clinical Practice Research Datalink, from January 1, 1998, through September 30, 2015, for patients aged 18 to 74 years who had mild hypertension (untreated blood pressure of 140/90-159/99 mm Hg) and no previous treatment. Anyone with a history of CVD or CVD risk factors was excluded. Patients exited the cohort if follow-up records became unavailable or they experienced an outcome of interest. Exposures: Prescription of antihypertensive medication. Propensity scores for likelihood of treatment were constructed using a logistic regression model. Individuals treated within 12 months of diagnosis were matched to untreated patients by propensity score using the nearest-neighbor method. Main Outcome(s) and Measure(s): The rates of mortality, CVD, and adverse events among patients prescribed antihypertensive treatment at baseline, compared with those who were not prescribed such treatment, using Cox proportional hazards regression Results: A total of 19 143 treated patients (mean [SD] age, 54.7 [11.8] years; 10 705 [55.9%] women; 10 629 [55.5%] white) were matched to 19 143 similar untreated patients (mean [SD] age, 54.9 [12.2] years; 10 631 [55.5%] female; 10 654 [55.7%] white). During a median follow-up period of 5.8 years (interquartile range, 2.6-9.0 years), no evidence of an association was found between antihypertensive treatment and mortality (hazard ratio [HR], 1.02; 95% CI, 0.88-1.17) or between antihypertensive treatment and CVD (HR, 1.09; 95% CI, 0.95-1.25). Treatment was associated with an increased risk of adverse events, including hypotension (HR, 1.69; 95% CI, 1.30-2.20; number needed to harm at 10 years [NNH10], 41), syncope (HR, 1.28; 95% CI, 1.10-1.50; NNH10, 35), electrolyte abnormalities (HR, 1.72; 95% CI, 1.12-2.65; NNH10, 111), and acute kidney injury (HR, 1.37; 95% CI, 1.00-1.88; NNH10, 91). Conclusions and Relevance: This prespecified analysis found no evidence to support guideline recommendations that encourage initiation of treatment in patients with low-risk mild hypertension. There was evidence of an increased risk of adverse events, which suggests that physicians should exercise caution when following guidelines that generalize findings from trials conducted in high-risk individuals to those at lower risk.